As decis??es do Conselho Administrativo de Recursos Fiscais desfavor??veis ao Fisco e o acesso ao Judici??rio - Santos, Marcos Paulo de Ara??jo (2015)
This study aims to make an analysis of whether or not the tax authorities to resort to the Judiciary way when, still in the harvest of the Board of Tax Appeals (CARF), obtains unfavorable decisions. Therefore, without any pretension of exhausting the topic , given its controversy nationwide and with few judged accordingly and dichotomous doctrinal understandings , especially discussing possible breach of the principle of inafastability of stamped jurisdiction in item XXXV of Article 5 of the Constitution 1988 Federal.